Rupture Life and Failure Mechanism of Grade 91 Steel Under the Influence of Notch Constraint - Imam Ul, Ferdous; N. A., Alang; J., Alias; A. H., Ahmad; Suraya, Mohd Nadzir (Springer Nature, 2023)
Coal-fired power plants must operate at higher temperatures and pressures to achieve maximum efficiency. During operation, components are exposed to the creep environment, which can lead to catastrophic plant failure. In this study, an initiative was taken to evaluate the creep behavior and failure mechanism of Grade 91 steel by conducting creep tests at 873 K and different stress levels. Two types of specimens (smooth and notched) were used to study the effects of uniaxial and multiaxial stress states on creep strength. Notched specimens with different acuities (2.28 and 4.56) were employed. The creep curve of both specimens showed all three stages known as primary, secondary, and tertiary. The secondary stage seems to be dominant in all three. The analysis of the creep life under the influence of net stress showed that the notched specimen had a longer creep life than the smooth specimen at the same stress level, indicating a "notch strengthening" effect. The effects of the representative stress were also evaluated, revealing that the von-Mises stress controls the rupture life. A comparative analysis of multiaxial ductility is made with various void-growth models. The Rice and Tracey model closely matches the experimental data at lower triaxiality, but the Cocks and Ashby and Splinder model overestimates the ductility. The fractography examination of the notched specimen revealed that, in comparison to the area at the root, the area towards the middle of the notch exhibits shallow dimples, indicating less plasticity. Meanwhile, the ruptured surface of smooth specimens shows that ductile dimples predominate.